2012
DOI: 10.1042/bj20111766
|View full text |Cite
|
Sign up to set email alerts
|

GRAS proteins: the versatile roles of intrinsically disordered proteins in plant signalling

Abstract: IDPs (intrinsically disordered proteins) are highly abundant in eukaryotic proteomes and important for cellular functions, especially in cell signalling and transcriptional regulation. An IDR (intrinsically disordered region) within an IDP often undergoes disorder-to-order transitions upon binding to various partners, allowing an IDP to recognize and bind different partners at various binding interfaces. Plant-specific GRAS proteins play critical and diverse roles in plant development and signalling, and act a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
178
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(182 citation statements)
references
References 86 publications
0
178
1
3
Order By: Relevance
“…Members within the same subfamily play similar regulatory roles, but in response to distinct signals, or play roles in crosstalk with many different signaling pathways in plant development by interacting with key proteins in these pathways. GRAS proteins are functionally required to accommodate different partners, and the intrinsically disordered nature of the N-domains facilitates the function of GRAS proteins as hub proteins and allows them to perform key roles in integrating multiple developmental and environmental signals (Sun et al, 2012a). As discussed previously, IDRs are able to efficiently recognize different partners in signaling via MoRF-partner interactions.…”
Section: Signal Transduction Proteins Gras Protein Familymentioning
confidence: 99%
See 1 more Smart Citation
“…Members within the same subfamily play similar regulatory roles, but in response to distinct signals, or play roles in crosstalk with many different signaling pathways in plant development by interacting with key proteins in these pathways. GRAS proteins are functionally required to accommodate different partners, and the intrinsically disordered nature of the N-domains facilitates the function of GRAS proteins as hub proteins and allows them to perform key roles in integrating multiple developmental and environmental signals (Sun et al, 2012a). As discussed previously, IDRs are able to efficiently recognize different partners in signaling via MoRF-partner interactions.…”
Section: Signal Transduction Proteins Gras Protein Familymentioning
confidence: 99%
“…It has been experimentally confirmed for many GRAS proteins that the LRI-VHIID-LRII pattern or individual motifs within the pattern are used for interactions with protein partners (Cui et al, 2007;Fode et al, 2008;Hirsch et al, 2009;Hou et al, 2010). Since the Leucine-rich regions were found to be involved in various types of transcriptional coactivation (Heery et al, 1997), it was speculated that the GRAS proteins act as transcriptional coactivators by either blocking or enhancing the transcriptional activity of their partners through the highly conserved LRI-VHIID-LRII pattern or entire GRAS domain (Sun et al, 2012a).…”
Section: Signal Transduction Proteins Gras Protein Familymentioning
confidence: 99%
“…The importance of this family has been made clear through a number of functional studies (Di Laurenzio et al, 1996;Peng et al, 1997;Silverstone et al, 1998), and a remarkable number of GRAS proteins have been identified in more than 294 embryophyta species (Finn et al, 2010;Sun et al, 2012). Most of these proteins play key roles in the transcriptional regulation and signaling transduction related to plant growth and development (Bolle, 2004;Achard et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…By phylogenetic analysis, the GRAS family can be divided into more than 10 subfamilies, of which SCL4/7 is one important subgroup (Sun et al, 2012). In Arabidopsis, SCL4 and SCL7 have similar expression levels under normal growth conditions; however, under stress conditions, SCL7 is upregulated while SCL4 is downregulated, indicating that SCL4/7 members could function as transcription factors in response to environmental stresses (Kilian et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These observations suggest that SLR1 functions as a positive regulator for the expression of GA down-regulated genes. Since DELLA proteins (including SLR1) have been considered to lack DNA-binding domains (Sun et al, 2012;Davière and Achard, 2013), they would need to interact with a TF to modulate DNA binding (Fig. 8,D and E).…”
Section: Involvement Of Gid2 and Gamyb In Ga-dependent Expression In mentioning
confidence: 99%